PENERAPAN LEMBAR KERJA BERBASIS INKUIRI PADA ANALISIS METABOLIT SEKUNDER BEBERAPA TANAMAN OBAT INDONESIAt - Shoyang Gadis Supratania; Saepudin Rahmatullah; Neneng Windayani (Jurnal Tadris Kimiya, 2021)
Secondary metabolites are part of the discussion of Natural Product Organic Chemistry which demands a practicum process in lectures. This research aims to determine process skills through the application of inquiry-based worksheets on secondary metabolite analysis of three types of Indonesian medicinal plants. In the worksheet, there were several expected goals, including developing students' abilities in designing experiments, conducting experiments, and communicating both orally and in writing. The method used in this research was a One-Shot Case Study with 18 students taking Natural Product Organic Chemistry courses. The instruments used were learning descriptions, inquiry-based worksheets, observation sheets, assessment sheets (psychomotor, presentations, and reports). The results of the worksheet application showed that the students' ability obtain an average value of 84.15 with a very good category. The ability to design experiments, conduct experiments, and communicate orally and in writing obtained results of 77.16 (good categories), 92.50 (very good), and 82.80 (very good), respectively. This inquiry-based worksheet can be used in the study of Natural Product Organic Chemistry, especially in secondary metabolites.